Exploring the gut microbiota-hippocampus-metabolites axis dysregulation in sepsis mice - Song, Fangqiang; Li, Qinglun; Cui, Jiyao; Wang, Jianhua; Xiao, Shuai; Yu, Bo; Sun, Yanqi; Song, Wenke; Wu, Linlin; Zhou, Yongqin (Frontiers in Microbiology, 2024)
Background: Sepsis is commonly associated with a sudden impairment of brain function, thus leading to significant rates of illness and mortality. The objective of this research was to integrate microbiome and metabolome to reveal the mechanism of microbiota-hippocampus-metabolites axis dysfunction in a mouse model of sepsis. Methods: A mouse model of sepsis was established via cecal ligation and puncture. The potential associations between the composition of the gut microbiota and metabolites in the hippocampus of mice with sepsis were investigated by combining 16S ribosomal RNA gene sequencing and ultra-high-performance liquid chromatography tandem mass spectrometry. Results: A total of 140 differential metabolites were identified in the hippocampal tissues of mice with sepsis when compared to those of control mice. These differential metabolites in mice with sepsis were not only associated with autophagy and serotonergic synapse, but also involved in the metabolism and synthesis of numerous amino acids. At the phylum level, the abundance of Bacteroidota was increased, while that of Firmicutes (Bacillota) was decreased in mice with sepsis. At the genus level, the abundance of Alistipes was increased, while that of Lachnospiraceae_NK4A136_group was decreased in mice with sepsis. The Firmicutes (Bacillota)/Bacteroidota (F/B) ratio was decreased in mice with sepsis when compared to that of control mice. Furthermore, the F/B ratio was positively correlated with 5'-methylthioadenosine, PC (18:3(9Z,12Z,15Z)/18:0) and curdione, and negatively correlated with indoxylsulfuric acid, corticosterone, kynurenine and ornithine. Conclusion: Analysis revealed a reduction in the F/B ratio in mice with sepsis, thus contributing to the disturbance of 5'-methylthioadenosine, curdione, PC (18:3(9Z,12Z,15Z)/18:0), corticosterone, ornithine, indoxylsulfuric acid and kynurenine; eventually, these changes led to hippocampus dysfunction. Our findings provide a new direction for the management of sepsis-induced hippocampus dysfunction.